A guide for positivist research paradigm: from philosophy to methodology/ Irwan Mohammad Ali - Mohammad Ali, Irwan (Universiti Teknologi MARA, Perak, 2024)
Asserting that reality is objective, observable, and governed by universal laws through empirical investigation and logical reasoning, positivism continues to serve as a foundation in scientific inquiry. This paper provides a thorough examination of the positivist research paradigm, tracing its philosophical underpinnings and methodological implications. The epistemological foundation of positivism rests on objectivism, which posits that knowledge is independent of individual perceptions and can be verified through empirical evidence. Ontologically, positivism asserts a realist perspective, asserting a singular reality that exists external to human cognition. Axiologically, positivism emphasises value-free research to ensure objectivity and replicability of findings. This paper explores these philosophical beliefs and their application in research design, data collection techniques such as surveys and experiments, and data analysis methods, including statistical tools like SPSS and SmartPLS. By interpreting these aspects, this paper serves as a comprehensive guide for researchers adopting a positivist research paradigm, offering insights into its strengths, limitations, and ongoing relevance in present scientific inquiry.